2017
DOI: 10.5958/0974-0279.2017.00032.5
|View full text |Cite
|
Sign up to set email alerts
|

Changing Crop Production Cost in India: Input Prices, Substitution and Technological Effects

Abstract: The study has examined economics of crop cultivation at the aggregate level over the past 25 years, identified sources of cost escalation and evaluated the effects of factor prices, substitution and technological effects on the production cost. The results reveal that a disproportionate change in gross return vis-à-vis cost resulted in varying rate of return from crop enterprise during the past 25 years. During 2007-08 to 2014-15, the average cost inflation reached the highest level of 13 per cent, more than h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…However, given the labour shortage during peak season and advantages of mechanisation such as labour saving, time saving and ensuring deep ploughing and so on, all sections of farmers have keen interest in using machines on custom hiring basis leading to a win-win situation. Bullock labour use for farm operations diminished over time from 14 per cent of the cost in TE 1990-91 to 5 per cent in TE 2014-15 and share of machine labour reversed from 7 per cent to 14 per cent (Srivastava et al 2017).…”
Section: Recent Innovations In Spread Of Farm Mechanisationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the labour shortage during peak season and advantages of mechanisation such as labour saving, time saving and ensuring deep ploughing and so on, all sections of farmers have keen interest in using machines on custom hiring basis leading to a win-win situation. Bullock labour use for farm operations diminished over time from 14 per cent of the cost in TE 1990-91 to 5 per cent in TE 2014-15 and share of machine labour reversed from 7 per cent to 14 per cent (Srivastava et al 2017).…”
Section: Recent Innovations In Spread Of Farm Mechanisationmentioning
confidence: 99%
“…In a very comprehensive study on costs and returns based on cost of cultivation data, Srivastava et al (2017) observed that cost of cultivation per hectare in real terms increased between 1990-91 and 2014-15. Farm mechanisation is one of the means that can potentially change the face of agriculture and lead to decline in costs.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies on the profitability of Indian agriculture (Raghavan, 2008;Tripathi, 2013;Srivastava et al, 2017). From most of these studies, it has been observed that the profitability of agriculture has declined considerably during the last few years, mainly due to increasing input cost leading to the agrarian crisis in India.…”
Section: Assessment Of Cost Of Paddy Cultivationin West Bengalmentioning
confidence: 99%
“…Narayanamoorthy 2013in one of his study opined that though the area under paddy cultivation and production have increased from 1950-51 to 2008-09, the paddy farmers have either faced losses or realised a very marginal profit, especially after the 1990s. In the context of paddy cultivation in West Bengal, Srivastava et al (2017) noted that in 2014-15, the cost of paddy production in this state was the highest among the 19 major paddy producing states in India. At the same time, the output cost ratio of paddy was lower than the output cost ratio of wheat, gram, arhar (split toor or tuvar dal known as pigeon peas), rapeseed and mustard, and sugarcane.…”
Section: Assessment Of Cost Of Paddy Cultivationin West Bengalmentioning
confidence: 99%
See 1 more Smart Citation